2021
DOI: 10.1002/eqe.3475
|View full text |Cite
|
Sign up to set email alerts
|

Seismic response study of ordinary and isolated bridges crossing strike‐slip fault rupture zones

Abstract: This article presents a comprehensive parametric study of ordinary and seismically isolated bridges crossing strike‐slip faults by performing nonlinear response history analysis using actual near‐fault ground‐motion records and by varying the fault crossing angle, fault crossing location, pier height, span length, seismic excitation polarity, and number of ground‐motion components. The considered ground motions include three records from major earthquakes with their peak ground displacements and pulse periods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Qiao et al (2022) conducted an in-depth parametric study of topographic effect on the seismic response and running safety of a train-bridge coupled system on a CRFB. Park et al (2004), Ucak et al (2014) and Yang et al (2021) presented seismic response study of ordinary and isolated bridges crossing strikeslip fault rupture zones by utilizing finite element models of the 10-span Bolu Viaduct.…”
Section: Introductionmentioning
confidence: 99%
“…Qiao et al (2022) conducted an in-depth parametric study of topographic effect on the seismic response and running safety of a train-bridge coupled system on a CRFB. Park et al (2004), Ucak et al (2014) and Yang et al (2021) presented seismic response study of ordinary and isolated bridges crossing strikeslip fault rupture zones by utilizing finite element models of the 10-span Bolu Viaduct.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the results indicated that, among the various FCAs analyzed, a 90 • angle resulted in smaller pylon displacement and longitudinal bearing displacement while leading to larger transverse bearing displacement. Lin et al [6], Yang et al [7], and Zeng et al [8] examined both ordinary and seismically isolated bridges crossing strike-slip faults. Their study systematically explored various factors, including FCA and fault-crossing location.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers evaluated the seismic fragility of multi-span CRFBs (Jung and Andrawes 2018;Abbasi and Moustafa 2019;Liang et al 2020;Shan et al 2020), conducted a parametric analysis of trainbridge interactions (Qiao et al 2023). Additionally, researchers have developed novel structural systems (Peng and Zhang 2020;Lin et al 2020c) and assessed the seismic response of ordinary and isolated CRFBs crossing strike-slip fault rupture zones (Ucak et al 2014;Yang et al 2021). However, existing studies have the following limitations: (1) the influence of different spans and pier heights on the seismic response of CRFBs has not been investigated; (2) the transverse whiplash effect and spatial torsion effect of CRFBs have not been investigated in detail; (3) few seismic control methods have been able to improve the seismic performance of CRFBs under near-fault ground motions (Xu et al 2017;Zhang and Xu 2022;Li and Xu 2023a).…”
Section: Introductionmentioning
confidence: 99%